2016
DOI: 10.1016/j.jeurceramsoc.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen permeation in symmetric and asymmetric La0.2Sr0.8Fe0.8Ta0.2O3−δ membranes

Abstract: La0.2Sr0.8Fe0.8Ta0.2O3-(LSFT) is a mixed ionic electronic conductor (MIEC) at elevated temperatures and as such a candidate material for applications both in syn-gas synthesis and as electrodes in solid oxide fuel cells (SOFC). This study addresses the variation in oxygen permeation rates for LSFT symmetric-and asymmetric-membranes at temperatures between 800 and 1000 o C with and without surface modification. The surface was strutured in two different scales, macro (porous LSFT-layer) and micro (acid etching)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Park et al 15 have reported a similar oxygen flux of 0.11 10 -2 ml.cm -2 .min -1 (8 10 -4 mol.m -2 .s -1 ) at 900°C with a La 0.6 Sr 0.4 Fe 0.8 Ti 0.2 O 3-δ dense membrane under an air/He gradient. Gurauskis et al 14 have reported a very high oxygen flux of 4.2 ml.cm -2 .min -1 (3.1 10 -2 mol.m -2 .s -1 ) at 900°C for a very thin (20 µm) dense La 0.2 Sr 0.8 Fe 0.8 Ta 0.2 O 3-δ membrane under an air/Ar-O 2 -H 2 gradient. However, La 1-x Sr x FeO 3-δ materials (LSF) have suitable mechanical properties and high electronic and ionic conductivities then, can therefore be used as dense membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al 15 have reported a similar oxygen flux of 0.11 10 -2 ml.cm -2 .min -1 (8 10 -4 mol.m -2 .s -1 ) at 900°C with a La 0.6 Sr 0.4 Fe 0.8 Ti 0.2 O 3-δ dense membrane under an air/He gradient. Gurauskis et al 14 have reported a very high oxygen flux of 4.2 ml.cm -2 .min -1 (3.1 10 -2 mol.m -2 .s -1 ) at 900°C for a very thin (20 µm) dense La 0.2 Sr 0.8 Fe 0.8 Ta 0.2 O 3-δ membrane under an air/Ar-O 2 -H 2 gradient. However, La 1-x Sr x FeO 3-δ materials (LSF) have suitable mechanical properties and high electronic and ionic conductivities then, can therefore be used as dense membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the surface of BSCF and LSCF samples sintered at 1150°C shows a secondary phase exclusively located at grain boundary at the sample surface, which decreases the ionic and electronic conductivities of the membrane material 9 . Thus, the research is currently interesting in the development of more stable materials without cobalt, containing lanthanum and iron by substituting Fe with a judicious cation in the B site like Al 10 , Cr 11 , Ga 12 13 , Ta 14 , Ti 15 16 . For instance, the oxygen flux is about 0.12 10 -2 ml.cm -2 .min -1 (8.…”
Section: Introductionmentioning
confidence: 99%
“…Although asymmetric membranes often show high semipermeation performances [27] [28] [29] [30], the rate-determining step of oxygen transport through the membrane is not clearly identified in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It provides the driving force for the oxygen separation, allowing oxygen ion transport from the high oxygen partial pressure side to the low oxygen partial pressure side. Membranes based on single MIEC materials can achieve high oxygen fluxes [8][9][10][11][12][13][14][15][16][17][18], however most of the promising materials are not chemically stable under atmosphere containing CO2 and SO2 [11,[19][20][21][22][23][24][25], which is particularly required for oxy-fuel combustion applications. Dual-phase composites consisting of separated ionic and electronic conductor phases are a promising alternative approach to ensure high oxygen flux and chemical stability in realistic power plant conditions.…”
Section: Introductionmentioning
confidence: 99%